Use of a Gum Elastic Bougie in a Penetrating Neck Trauma. Issue 2 (28th February 2014) - Daniel, Yann; de Regloix, Stanislas; Kaiser, Eric
Abstract The case of a patient with a zone II penetrating neck injury who was intubated successfully utilizing the gum elastic bougie (GEB) is reported. He presented at a forward operational base in Afghanistan with a shrapnel wound in his neck as well as a cough and hoarseness. There were two wounds on each side of his laryngeal cartilages. The patient's breathing rate gradually increased and labored inhalation developed while the aeromedical evacuation was delayed for tactical reasons. Subcutaneous emphysema and edema concealed the anatomical landmarks, making a cricothyrotomy unsafe, and no fiber optic devices were available on site. Intratracheal intubation was decided upon by the doctors involved. Because of the anticipated difficultly of intubation, the GEB was used from the outset. During direct laryngoscopy, edema, blood, and mucus concealed the anatomic reliefs of the larynx. The glottis was not visible. On the second attempt, "clicks" were clearly perceived and the tube was railroaded over the bougie. Finally, the patient was evacuated to an Afghan military hospital. In this report, the benefit-risk balance for the use of the GEB in penetrating neck trauma is discussed. Although the use of the GEB cannot be recommended in all cases of penetrating neck injury, it should be considered as an option. This technique is not without risk, but in very remote settings or hostile environments, especially when cricothyrotomy is not possible, it can be lifesaving. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>Y</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Daniel</surname> </string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>de Regloix</surname></string-name>, <string-name><given-names>E</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Kaiser</surname></string-name>. Use of a gum elastic bougie in a penetrating neck trauma . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>2</issue>):<fpage>1</fpage>-<lpage>2</lpage></mixed-citation>.